Sorafenib and rapamycin induce growth suppression in mouse models of hepatocellular carcinoma - Huynh, Hung (J Cell Mol Med, 2009)
Hepatocellular carcinoma (HCC) is the fifth most common malignancy worldwide. Vascular endothelial growth factor, platelet derived growth factor and the Raf/mitogen‐activated protein kinase/extracellular signal regulated kinase (Raf/MEK/ERK) signalling pathway regulates the growth, neovascularization, invasiveness and metastatic potential of HCC. In this study, we investigated the in vivo antitumour activity and mechanisms of action of sorafenib tosylate on four patient‐derived HCC xenografts. Sorafenib dosed at 50 mg/kg and 100 mg/kg inhibited tumour growth by 85% and 96%, respectively. Sorafenib‐induced growth suppression and apoptosis were associated with inhibition of angiogenesis, down‐regulation of phospho‐platelet‐derived growth factor receptor β Tyr1021, phospho‐eIF4E Ser209, phospho‐c‐Raf Ser259, c‐Raf, Mcl‐1, Bcl‐2, Bcl‐x and positive cell cycle regulators, up‐regulation of apoptosis signalling kinase‐1, p27 and p21. Expression of IGF‐1Rβ and phosphorylation of c‐Raf Ser338, MEK1/2 Ser217/221 and ERK1/2 Thr202/Tyr204 were increased by sorafenib treatment. Phosphorylation of mammalian target‐of‐rapamycin (mTOR) targets (p70S6K, S6R and 4EBP1) was reduced by sorafenib in sorafenib‐sensitive lines but activated in sorafenib‐less‐sensitive 10–0505 xenograft. Sorafenib‐induced phosphorylation of c‐met, p70S6K and 4EBP1 was significantly reduced when 10–0505 cells were co‐treated with anti‐human anti‐HGF antibody, suggesting that treatment with sorafenib leads to increased HGF secretion and activation of c‐met and mTOR targets. Treatment of 10–0505 tumours with sorafenib plus rapamycin resulted in growth inhibition, inhibition of vascular endothelial growth factor receptor‐2 phosphorylation, increased apoptosis and completely blocked sorafenib‐induced phosphorylation of mTOR targets and cyclin B1 expression. These data also provide a strong rationale for clinical investigation of sorafenib in combination with mTOR inhibitors in patients with HCC.